2022
DOI: 10.3390/nano12020256
|View full text |Cite
|
Sign up to set email alerts
|

Porous Polydimethylsiloxane Elastomer Hybrid with Zinc Oxide Nanowire for Wearable, Wide-Range, and Low Detection Limit Capacitive Pressure Sensor

Abstract: We propose a flexible capacitive pressure sensor that utilizes porous polydimethylsiloxane elastomer with zinc oxide nanowire as nanocomposite dielectric layer via a simple porogen-assisted process. With the incorporation of nanowires into the porous elastomer, our capacitive pressure sensor is not only highly responsive to subtle stimuli but vigorously so to gentle touch and verbal stimulation from 0 to 50 kPa. The fabricated zinc oxide nanowire–porous polydimethylsiloxane sensor exhibits superior sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…As summarized in Figure 3e, we compared our double‐layered sensor with other sensors from recent studies using the microstructure. [ 53–63 ] The comparison result showed that this double‐layer structure sensor had the distinctively lowest sensitivity loss (about 0.0195% kPa −1 ) with the widest pressure detection range (see details in Table S1, Supporting Information), outperforming other capacitive pressure sensors reported in the literature to the best of our knowledge.…”
Section: Resultsmentioning
confidence: 92%
“…As summarized in Figure 3e, we compared our double‐layered sensor with other sensors from recent studies using the microstructure. [ 53–63 ] The comparison result showed that this double‐layer structure sensor had the distinctively lowest sensitivity loss (about 0.0195% kPa −1 ) with the widest pressure detection range (see details in Table S1, Supporting Information), outperforming other capacitive pressure sensors reported in the literature to the best of our knowledge.…”
Section: Resultsmentioning
confidence: 92%
“…However, they have been mainly been used for applications such as imaging [31] and wearables [29,30] in the underwater environment, and not necessarily to measure the water pressure itself. For this reason, the sensors have been tested in a limited water depth and low-pressure range (usually <10 kPa) [32]. An array of solid PDMS based capacitive pressure sensing system is another example that displays excellent performance in deep sea-water [33].…”
Section: State Of the Artmentioning
confidence: 99%
“…Using a porous elastomer as the dielectric layer can effectively improve the sensitivity of capacitive pressure sensors by expelling air from the porous elastomer during compression [ 37 ]. The structure of the porous elastomer can increase the compressibility of the dielectric layer and make the dielectric layer easier to deform.…”
Section: Transduction Mechanismsmentioning
confidence: 99%